The theory of learning : an introduction - Cotton, Julie (London ; Philadelphia : Kogan Page, 1995)
This study aims to provide teachers and lecturers with an understanding of the many influences which affect individual learners. Drawing on a range of theories, the author offers guidance to help teachers spot and overcome different obstacles to learning.
Includes bibliographical references
Keywords: Learning; Psychology of